PENGARUHINTENSITASINFORMASITENTANGBERITA DEMOBUPATIPATI DIMEDIASOSIALTERHADAP PERSEPSI MASYARAKATPATIMENGENAIGAYA KOMUNIKASISUDEWO - Audy Aprilia; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The demonstrations by the people of Pati Regency in August 2025, triggered by the 250% increase in the state tax (PBB-P2) and the controversial response of the Pati Regent, received widespread attention on social media. The high level of news coverage is suspected to have influenced public perception of the event. This study aims to determine the effect of the intensity of information about the Pati Regent's demonstration on social media on the perceptions of Pati residents regarding Sudewo's communication style. The study employed cultivation theory with a quantitative explanatory approach. The sample consisted of 100 respondents from Pati Regency residents aged 17 and over, eligible to vote, and active social media users. Data were collected through Gform and analyzed using simple linear regression. The results indicate that the intensity of information about the Pati Regent's demonstration on social media has a positive and significant effect on public perception. This is evidenced by a significance value of <0.001 and a calculated t-value of 14.938, which is greater than the t-table of 1.660. The coefficient of determination (R Square) of 0.695 indicates that news exposure explains 69.5% of the variation in public perception. This finding suggests that the greater the public's exposure to news on social media, the greater its influence on the formation of public perception.